Pectin limits epithelial barrier disruption by Citrobacter rodentium through anti-microbial effects. Issue 2 (7th January 2021) - Beukema, M.; Ishisono, K.; de Waard, J.; Faas, M. M.; de Vos, P.; Kitaguchi, K.
Abstract : Pectins inhibit the growth of C. rodentium in vitro, preventing attachment of C. rodentium to CMT93 epithelial cells. Through these antimicrobial effects, pectins protect the epithelium from C. rodentium -induced barrier dysfunction and damage. Abstract : Scope : C. rodentium is the murine equivalent of Enteropathogenic Escherichia. coli (EPEC) and Enterohemorrhagic Escherichia coli (EHEC) which induce damage to the intestinal epithelial barrier that results in diarrhea and intestinal inflammation. Dietary fibre intake can be an effective approach to limit epithelial damage by these enteric pathogens. Therefore, the protective effect of dietary fibre pectin against dysfunction of epithelial barrier integrity upon C. rodentium infection was investigated. Methods and results : Pectins that structurally differed in the degree and distribution of methylesters were tested on barrier protective effects on epithelial cells against C. rodentium by measuring transepithelial electrical resistance and lucifer yellow fluxes. All three pectins protected the epithelial barrier from C. rodentium induced damage in a structure-independent manner. These barrier protective effects were also independent of pectin-induced TLR2 activation. Furthermore, the pectins induced anti-adhesive effects on C. rodentium by interacting with C. rodentium and not with epithelial cells. This may be explained by antimicrobial effects of pectins on C. rodentium and not on other enteric bacteria including Lactobacillus plantarum and E. coli . A competition ELISA for binding of C. rodentium to pectin supported this finding as it showed that pectin interacts strongly with C. rodentium, whereas it interacts weakly or not with L. plantarum or E. coli . Conclusion : These findings demonstrate that pectin protects the epithelial barrier from C. rodentium induced damage by inducing anti-microbial effects.